The Battle of Britain : New Perspectives : Behind the Scenes of the Great Air War - Ray, John Philip, 1929- (London : Brockhampton Press, 1999)
"The story of how RAF fighters defeated the Luftwaffe in 1940 and saved Britain from invasion is a well known national tradition, but over a decade of new research has allowed reassessment of significant elements of the battle. Central to all these is the personality clashes behind the scenes in the RAF that frequently threatened to be more dangerous than the Luftwaffe attacks. The author examines why Dowding commanded his squadrons in the well-known tactics, but how every day he was under personal attack from rivals for his position and from enemies throughout the Air Ministry who wanted different ideas and defences, despite the severity of the threat and Dowding's success. Also examined is the effect of this on the air fighting, a detailed view from the Luftwaffe side and finally an answer as to why Dowding was immediately retired at the end of his finest hour to obscurity and never rewarded as every other successful commander was." --Amazon.com
Introduction -- Dowding's Position in Jult 1940 -- the Threat from the Luftwaffe -- The Opening Phase of Battle, 10 July to 18 August -- The Development of the Big Wing Controversy, 19 August to 7 September -- The Battle Within a Battle, 7 September to 16 October -- Night Air Defence -- Changes at Fighter Command -- Epilogue.
Originally published: London: Arms & Armour, 1994.
Includes bibliographical references (pages 210-216) and index.
Keywords: Britain, Battle of, Great Britain, 1940.; World War, 1939-1945 -- Campaigns -- Great Britain; Military operations, Aerial; Great Britain